Siriah Ka Sidang as an Indigenous Mechanism for Customary Forest Governance in Minangkabau - Febri Yulika; Septriani; Endrizal (International Journal of Asia Pacific Studies, 2026)
This study examines how siriah ka sidang, a customary conflict resolution mechanism practised by the indigenous community of Nagari Pasia Laweh, West Sumatra, contributes to ecological sustainability, social cohesion, and culturally legitimate justice. It addresses two questions: (1) How is siriah ka sidang practised? and (2) How does it influence forest governance, the preservation of ecological knowledge, and the reduction of long-term conflicts? A descriptive qualitative approach was employed, with data collected through in-depth interviews, focus group discussions (FGDs), and participatory observation conducted between June 2025 and May 2026. The findings identify three key principles. First, hearings are convened only after community members submit reports supported by sufficient evidence of customary law violations. Second, proceedings take place only when both parties voluntarily agree to participate, fulfil the required procedures, and accept the final decision. Third, the mechanism prioritises reconciliation, collective responsibility, and environmental stewardship rather than punishment, thereby supporting sustainable forest governance, preserving ecological knowledge, and preventing long-term conflicts. This study concludes that siriah ka sidang reflects the principles of the green economy and exemplifies embedded ecological governance, in which ecological management is rooted in cultural values, customary institutions, local beliefs, and community relationships while promoting a restorative model of justice perceived as more legitimate and effective than alternative dispute-resolution mechanisms.